Ensuring Women's Sexual And Reproductive Health Rights: A Comparative Study of Sri Lanka's Legal And Policy Framework With Nepal - Dissanayake, V.G.E.S.W (The Department of Law, Faculty of Arts, University of Jaffna / Surana and surana International Attorneys India, 2025)
The recognition and protection of women's sexual and reproductive health rights (SRHR) are fundamental to their overall well-being and for achieving gender equality and advancing public health in Sri Lanka. The study expects to analyse the legal and policy frameworks governing sexual and reproductive health rights in Sri Lanka as compared to that of Nepal, a regional counterpart that has made significant strides in this area. The Constitution of Sri Lanka, public health policies, and specific legislative measures mandate certain aspects of women’s health and rights, but generally, these do not extend much towards comprehensive protection in such areas as access to contraception, safe abortion services, and education on reproductive health. Cultural and societal stigmas further exacerbate the challenges faced by women in exercising these rights. Conversely, Nepal’s progressive reforms in SRHR, including constitutional guarantees, the liberalization of abortion laws and the enactment of Safe Motherhood and Reproductive Health Rights Act in 2018 provide a compelling model. By integrating international human rights standards and actively engaging civil society, Nepal has significantly improved access to reproductive healthcare services and awareness. This research adopts a qualitative methodology, drawing on doctrinal analysis of laws, policies, and international obligations, as well as comparative legal analysis between the two countries. Key findings highlight that Sri Lanka lacks a holistic approach to SRHR, with gaps in implementation and limited legal recognition of women’s autonomy in reproductive decisions. The study puts forth a proposed road map for legal and policy reforms in Sri Lanka aimed at improving the protection of women's health and dignity and calls for dedicated legislative measures similar to Nepal.
Keywords: Sexual and reproductive health rights; Gender equality; Human rights; Sri Lanka; Nepal